Development of An Islamic Values Based E-Module for Vocational Culinary Skills on Occupational Safety and Health for Students with Mild Intellectual Disabilities - Agmi Almanawara; Atien Nur Chamidah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study aims to: (1) develop an Islamic-value based e-module for vocational culinary skills focusing on occupational safety and health (OSH) for students with mild intellectual disabilities; (2) determine the feasibility of the e-module based on expert evaluations; and (3) examine the usefulness and effectiveness of the developed e-module. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. Validation was conducted by one subject-matter expert, one media expert, and three teachers. The usefulness and effectiveness trials involved eight students with mild intellectual disabilities at a state special school (SLBN) in Bengkulu City, Indonesia. Data were analyzed using qualitative and quantitative descriptive analysis. The results indicate that: (1) the Islamic values–based OSH e-module for culinary vocational skills was successfully developed as a learning resource that emphasizes safety, caution, and responsibility in the workplace, in line with the Islamic principle of safeguarding human life (ḥifẓ al-nafs); (2) feasibility evaluation results showed that the subject-matter expert awarded a score of 97% (“Highly Feasible”), the media expert 83.2% (“Highly Feasible”), and the teachers 92.3%, 94%, and 97%, respectively (all categorized as “Highly Feasible”); and (3) the trial results demonstrated a usefulness level of 94% (“Highly Useful”), along with a statistically significant difference between pre-test and post-test scores (p = 0.011). Therefore, the Islamic values–based OSH e-module for culinary vocational skills is considered feasible, useful, and effective for vocational learning among students with mild intellectual disabilities.